FUNCTIONAL-PRAGMATIC FEATURES OF GRAMMATICAL COMPRESSION IN UZBEK AND ENGLISH HEADLINES IN DIGITAL AND PRINT MASS MEDIA DISCOURSE - Turgunova Fazilat Rustam qizi (Sciental Journals Publishing, 2026)
This article provides a comparative analysis of the functional-pragmatic features of grammatical compression in Uzbek and English headlines within digital and print mass media discourse. The study identifies grammatical compression strategies used in headlines, their information density, degree of semantic preservation, and impact on the audience. It reveals how the communicative requirements of digital and print media formats influence the formation of grammatical compression models. The findings show that the omission of auxiliary elements and the predominance of nominative constructions are characteristic of English, whereas morphological compactness and syntactic flexibility function as the main mechanisms of compression in Uzbek. The conclusions of the study are of theoretical and practical significance for the investigation of headline discourse within media linguistics and comparative linguistics.
Keywords: Grammatical compression, media discourse, headline, functional-pragmatic analysis, digital and print mass media, Uzbek and English languages, language economy.